Designing Scholarly Introductions as Jobs to Be Done. (April 2022) - Simsek, Zeki; Li, Sali
This is the first editorial commentary in a three-part series that addresses introductions, implications, and interestingness. The first, focusing on the introduction design, is about what the beginning of a paper should look like. The second, focusing on practice implications, is about what the end of a paper should look like. The third discusses how to develop and fit attention-grabbing ideas into the academic conversation in the literature. We hope this editorial series provides inspiration and ideas about publishing papers that people want to engage with.